Fluorescent in situ hybridization of human sperm – diagnostics, indications, and therapeutic implications - Ramasamy, Ranjith (Fertil Steril, 2014)
Male factor infertility is a relatively common condition, affecting at least 6% of men of reproductive age. Typically men with unknown genetic abnormalities resort to using assisted reproductive technologies (ART) to achieve their reproductive goals. Infertile men who father biological children using ART could have a higher incidence of aneuploidy, which is a deviation from the normal haploid or diploid chromosomal state. Aneuploidy can be evaluated using fluorescent in situ hybridization (FISH), a cytogenetic assay that gives an estimate of the frequencies of chromosomal abnormalities. The chromosomes that are generally analyzed in FISH are associated with aneuploidies that are compatible with life, that is, chr.13, 18, 21, X, and Y. The technique is indicated for a variety of reasons, but most importantly in the following: 1) men who despite normal semen parameters suffer recurrent pregnancy loss and 2) men with normal semen parameters, undergoing IVF, but still experiencing recurrent implantation failure. It may be used as a screening tool to help in reproductive and genetic counseling of affected couples, or those who have previously experienced failure of ART. A qualitative analysis of FISH study results allows them to make informed reproductive choices. Given its increasing clinical use in various infertility diagnoses and the development of novel adjunct technologies, one can expect much progress in the areas of preimplantation genetic screening, diagnostics, and therapeutics.